The Role of Muhammadiyah Education in Dealing with Bid’ah: E-Learning about Al-Islam and Kemuhammadiyahan - Wardiyanto Wardiyanto; Hasnidar Hasnidar; Elihami Elihami (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
Muhammadiyah education is an Islamic da'wah movement that from the beginning voiced anti-Tahayul Bid'ah and Churafat, which is commonly abbreviated as TBC, to be the main pioneer in inviting Muslims to only return to the Koran and Sunnah in matters of faith and worship. By keeping away from heretical practices of worship or acts of worship that are not religiously guided. In the case of Muhammadiyah, it uses the anti-bid'ah paradigm by defining bid'ah in all worship activities that require the kaifiat kaifiat as separate. That Bid'ah is a pattern and procedure that resembles the guidance of the Shari'a with the intention of worshiping Allah excessively, or pursuing excessive obedience and obedience and without guidance from Allah and His Messenger, that is what Muhammadiyah sees as heresy.